The influence of COVID-19 pandemic on the global business trends and management practices - Natasha Ristovska; Daliborka Blazheska; Sashko Gramatnikovski (UTMS Journal of Economics, 2023)
COVID-19 has had a significant impact on the global economic activities. Businesses entities experienced the disruption of their normal operations. The dynamic nature of modern working conditions and the pivotal role of change management approaches in navigating this complexity is analysed. Pandemic-induced changes in the working environment, global workforce and productivity, sales and profit, as well as consumer behavior and management practices are highlighted in this paper. Analysis of the competition and market challenges caused by the pandemic is also provided. Additionally, an overview of the various aspects how businesses organizations have adapted to the challenges posed by the pandemic is presented with emphasis on the need for organizational changes in response to the pandemic.
Keywords: M10; M21; L20; 330; pandemic; business; sustainability; resilience; organizational changes; agile change management